Effectiveness of platelet-rich fibrin in the treatment of intrabony defects with or without bone graft: A clinical comparative study - Mohammed Ahsan Razi; Shandar Siddiqui; Ankit Mahajan; Seema Qamar; Puja Kumari; Soni Kumari (Wolters Kluwer Medknow Publications, 2021)
Background: Periodontal diseases are a group of inflammatory diseases causing alveolar bone loss and eventually leading to loss of teeth. The present study was evaluated the effectiveness of platelet-rich fibrin (PRF) in the treatment of intrabony defects with or without bone graft. Materials and Methods: Thirty subjects with the presence of intrabony defects were enrolled. All subjects were included irrespective of age and gender. A questionnaire was prepared for extracting demographic and personal details of all the patients. William probe and moth mirror-tweezers set was used for carrying out clinical examination of all subjects. Random and unbiased division of all the subjects was done with ten patients in each group as follows: Group I: Subjects in which treatment was carried out using PRF with demineralized bone matrix, Group II: Subjects in which treatment was carried out using PRF alone, and Group III: Subjects in which treatment was carried in the form of open flap debridement (OFD). Pretreatment and posttreatment clinical variables were assessed which included plaque index (PI), gingival index (GI), probing depth (PD), relative attachment level (RAL), and gingival recession (GR) were assessed at baseline and 9 months postoperatively were calculated. Results: Mean PI among Group 1, Group 2, and Group 3 at baseline was 0.78, 0.8, and 0.84, respectively. Mean PI among Group 1, Group 2, and Group 3 at 9 months follow-up was 0.56, 0.55, and 0.72, respectively. Significant results were obtained while comparing the PI among the three study groups at follow-up. Mean GI among Group 1, Group 2, and Group 3 at baseline was 0.78, 0.8, and 0.84, respectively. Mean GI among Group 1, Group 2, and Group 3 at 9 months follow-up was 0.56, 0.55, and 0.72, respectively. Significant results were obtained while comparing the GI among the three study groups at follow-up. Significant difference was seen in PD, RAL, and GR from baseline to 9 months in all groups (P < 0.05). Conclusion: PRF leads to significantly better improvement in the clinical parameters on follow-up in comparison to OFD alone in patients with the presence of intrabony defects.